HUBUNGAN ANTARA AKTIVITAS MENCOCOK GAMBAR DENGAN KEMAMPUAN MOTORIK HALUS ANAK USIA DINI(Penelitian Korelasi di Kelompok B RA Ash-Shiddiq Cileunyi) - Tasya Aida; Ida Rosyidah; Zaenal Muftie (CV. Adiba Aisha Amira, 2025)
Based on this research, there is an imbalance between the picture-matching activity and fine motor skills in children in Group B at RA Ash-Shiddiq Cileunyi. The purpose of this study is to examine the children's activity in matching pictures, the fine motor skills of early childhood children, and the relationship between picture-matching activities and fine motor skills in early childhood children. This study uses a correlational approach based on a large number of subjects. The subjects of this study are children from Group B1 and B2, totaling 31 children, consisting of 18 boys and 13 girls. The data collection methods include observation and note-taking. The results obtained from the picture-matching process show an average score of 54, which falls within the range of 50-59, categorized as weak. The fine motor skills of the children received an average score of 78, which falls within the range of 70-79, categorized as good. Additionally, a correlation of 0.98 was found between the picture-matching performance and the fine motor skills of the children. The hypothesis test was conducted using a t-test, and the t_(calculated) = 26.35, while the t_(table) value at a 5% significance level with 29 degrees of freedom is 2.045. Therefore, since t_(calculated) = 26.35 > t_(table) = 2.045, it can be concluded that the picture-matching activity for early childhood children in Groups B1 and B2 supports the alternative hypothesis, and the null hypothesis is rejected. The results show that 96% of the activity is related to picture matching, while 4% is related to other activities.